Tightly Sealed 3D Lipid Structure Monolithically Generated on Transparent SU-8 Microwell Arrays for Biosensor Applications - Kang, Dong-Hyun; Han, Won Bae; Choi, Nakwon; Kirn, Yong-Jun; Kim, Tae Song (American Chemical Society, 2018)
Artificial lipid membranes are excellent candidates for new biosensing platforms because their structures are similar to cell membranes and it is relatively easy to modify the composition of the membrane. The freestanding structure is preferable for this purpose because of the more manageable reconstitution of the membrane protein. Therefore, most of the lipid membranes for biosensing are based on two-dimensional structures that are fixed on a solid substrate (unlike floating liposomes) even though they have some disadvantages, such as low stability, small surface area, and potential retention of solvent in the membrane. In this paper, three-dimensional freestanding lipid bilayer (3D FLB) arrays were fabricated uniformly on SU-8 microwells without any toxic solvent. The 3D FLBs have better stability and larger surface area due to their cell-like structure. In order to improve the sealing characteristics of the 3D FLBs, the applied frequency of the ac field was controlled during the electroformation. The 3D FLBs were observed through transparent SU-8 microwell arrays using confocal microscopy and demonstrated perfect sealing until 5.5 days after the electroformation at more than 1 kHz. Also, the details of the sealing of a fixed 3D freestanding lipid structure were discussed for the first time. The unilamellarity and biofunctionality of the 3D FLBs were verified by a transport protein (alpha-hemolysin) assay.
Keywords: GIANT VESICLES; CONTROLLED SIZE; ELECTROFORMATION; LIPOSOMES; HYDRATION; BILAYERS; WATER